PENGARUH AKUPRESUR PERIKARDIUM 6 TERHADAP MUAL MUNTAH KEHAMILAN KURANG 16 MINGGU - Djanah, Nur; Hadisaputro, Suharyo; Hardjanti, Triana Sri (Jurnal Kesehatan Ibu dan Anak, 2014)
Nausea and vomiting in pregnancy is a common problem, which can be serious for both mother and baby. More than half (50-90%) of pregnant women experiencing nausea vomiting. Numerous attempts have been made to reduce the nausea vomiting with pharmacological and nonpharmacological approaches. Acupressure Pericardium 6 is one of the non-pharmacological approach, which is related closely to acupuncture, is considered as a key point in reducing the symptoms of nausea and vomiting, but some studies show contradictory results. The purpose of this research was to describes the effect of acupressure Pericardium 6 to decrease the frequency of nausea vomiting of pregnancy less 16 weeks.The design used was randomized pre-post test control group design. Total sample 33 consists of 17 intervention group and 16 control group, who meets the criteria of inclusion and exclusion. The mother?s age, gravidity, obesity levels and hiperemesis gravidarum history matched between groups. The intervention group were given a treatment of acupressure on acupoint Pericardium 6, while the control group acupressure on three fingers on top of acupoint Pericardium 6, it was done every 5 minutes for four days. There are significant differences on decreases of the duration of nausea (p = 0.002) and episodes of nausea vomiting (p = 0,015) between the intervention group and control group after intervention, while episodes of retching vomiting there are no significant differences (p = 0,159). The conclusion was that the acupressure Pericardium 6 can decreases of the frequency of nausea vomiting of pregnancy. Acupressure Pericardium 6 can be applied as a non-pharmacological therapy to decrease frequency of nausea vomiting in pregnancy less than 16 weeks.